Biological and genomic characterization of three psychrophilic Y. enterocolitica phages - Hammerl, Jens A.; Pham, Minh Anh; El-Ahmad, Shirin; Manta, Diana; Jäckel, Claudia; Hertwig, Stefan (Frontiers in Microbiology, 2024)
Yersinia (Y.) enterocolitica is an important foodborne pathogenic species that is mainly transmitted by the consumption of contaminated meat, particularly pork. To combat the bacteria along the food chain, the application of strictly lytic phages may be a promising tool. As the temperatures in the gut of animals and during food processing can differ significantly, a phage cocktail intended to be used for applications should comprise phages that are active at various temperatures. In this study, we isolated and characterized three phages with a myoviridal morphology (vB_YenM_P8, vB_YenM_P744 and vB_YenM_P778), which lysed the most important Y. enterocolitica serotypes O:3, O:9 and O:5,27 at a low multiplicity of infection (MOI) and at low temperatures down to 6 °C. While vB_YenM_P8 is a member of the T4 family, vB_YenM_P744 and vB_YenM_P778 are novel phages that do not show relationship to known phages. The three phages were mixed in a cocktail with the already described phages vB_YenM_P281 and vB_YenP_Rambo. The cocktail revealed a strong lytic activity and lysed a mixture of Y. enterocolitica serotypes at room temperature (RT) within few hours with a reduction of up to 4.8 log10 units.Moreover, at even lower temperatures down to 6 °C, the mixture was significantly reduced after incubation overnight. The strongest reductions were determined at 6°C (4.0 log10 units) suggesting that the cocktail can lyse the psychrophilic Y. enterocolitica also during food processing. To determine possible phage resistance, 100 colonies that survived the infection by the phages were isolated and analysed regarding their serotype and phage susceptibility. Most isolates belonged to serotype O:9, but all of them were still sensitive to at least one phage of the cocktail.